Comparison of heat dissipation response between Malaysian and Japanese males during exercise in humid heat stress - Wakabayashi, Hitoshi; Wijayanto, Titis; Lee, Joo-Young; Hashiguchi, Nobuko; Saat, Mohamed; Tochihara, Yutaka (International journal of biometeorology, 2011)
This study investigated the differences in heat dissipation response to intense heat stress during exercise in hot and humid environments between tropical and temperate indigenes with matched physical characteristics. Ten Japanese (JP) and ten Malaysian (MY) males participated in this study. Subjects performed exercise for 60 min at 55% peak oxygen uptake in 32°C air with 70% relative humidity, followed by 30 min recovery. The increase in rectal temperature ( T re ) was smaller in MY during exercise compared to JP. The local sweat rate and total body mass loss were similar in both groups. Both skin blood flow and mean skin temperature was lower in MY compared to JP. A significantly greater increase in hand skin temperature was observed in MY during exercise, which is attributable to heat loss due to the greater surface area to mass ratio and large number of arteriovenous anastomoses. Also, the smaller increase in T re in MY may be explained by the presence of a significantly greater core–skin temperature gradient in MY than JP. The thermal gradient is also a major factor in increasing the convective heat transfer from core to skin as well as skin blood flow. It is concluded that the greater core–skin temperature gradient observed in MY is responsible for the smaller increase in T re .